Performance analysis and construction scheme proposal of 5G network at 700 MHz band - Peiquan FAN; Ailing WEI; Dongchen ZHANG; Xingzheng LI (Dianxin kexue)
5G network opens a new stage of mobile Internet and effectively promotes industrial automation and social development.In order to promote the construction and development of 5G network, the demand of 700 MHz band applied to 5G network was analyzed, took the lead in organizing field test and detailed analysis, 700 MHz 5G network construction scheme based on the test result was discussed, so as to guide 5G base station deployment and antenna parameter configuration.